Note—Removing a Self-Imposed Restriction in Modelling Hierarchical Decision Processes - Ruefli, Timothy W.; Storbeck, James (Management Science, 1984)
Models of decision-making in multi-level, hierarchical systems in the literature have been restricted to structures where the system is strictly pyramidal in nature. We will show that this restriction has been self-imposed and that existing models can be modified to represent a wide range of nonpyramidal structures.